L’immagine dell’Oriente nella Commedia dell’Arte sull’esempio di commedie e canovacci secenteschi scelti .......... 231 - Surma-Gawłowska, Monika (Pensées orientale et occidentale : influences et complémentarité II, 2021)
THE IMAGE OF THE ORIENT IN COMMEDIA DELL’ARTE ON THE EXAMPLE OF SELECTED 17TH CENTURY CANOVACCI AND COMEDIESThe paper analyses the presence of Oriental themes in the most important canovacci and comedies of the Italian 17th century theatre. Those themes are considered another evidence of the attention paid by professional comedians to current political and social subjects.